PREVALENCE OF GENITAL MYCOPLASMA INFECTION AND ASSOCIATED FACTORS IN WOMEN WITH PRIMARY INFERTILITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the prevalence of genital Mycoplasma infection and associated factors among women with primary infertility.Methods: A cross-sectional study was conducted on 78 women diagnosed with primary infertility at the Center for Reproductive Endocrinology and Infertility, Hue University of Medicine and Pharmacy Hospital. Participants underwent testing for sexually transmitted pathogens, including genital Mycoplasma.Results: The prevalence of genital Mycoplasma infection in women with primary infertility was 41% (95% CI: 29.9-52.2%), of which Ureaplasma parvum infection (32.1%), Ureaplasma urelyticum (3.8%), co-infection  with Ureaplasma parvum and Ureaplasma urelyticum (5.1%). No cases of Mycoplasma hominis or Mycoplasma genitalium infection were reported. There were no significant associations between genital mycoplasma infection and demographic or clinical characteristics, including age, occupation, educational level, medical history, menstrual characteristics, and sexual behaviors. However, women with a history of infertility treatment had a higher risk of genital Mycoplasma infection compared with those without such history (ORadj = 5.67; 95% CI: 1.50-21.45; p = 0.010), after adjusting for age, education and occupation.Conclusion: Genital Mycoplasma infection is a noteworthy concern among women with primary infertility, with Ureaplasma parvum being the most frequently detected pathogen. Screening and management of genital infections in women with primary infertility should pay particular attention to those with a history of infertility treatment.
Keywords: Genital Mycoplasma, primary infertility, women, STDs.